1993
DOI: 10.1002/mc.2940070405
|View full text |Cite
|
Sign up to set email alerts
|

Association of protein kinase C activation with induction of ornithine decarboxylase in murine but not human keratinocyte cultures

Abstract: The goal of this study was to compare the response of mouse epidermal keratinocytes (MEKs) and human epidermal keratinocytes (HEKs) to 12-O-tetradecanoylphorbol-13-acetate (TPA) with respect to the activation and downregulation of protein kinase C (PKC), the expression of c-jun and c-fos, and the expression and induction of ornithine decarboxylase (ODC) activity. Keratinocytes from adult CD-1 mice and from discarded adult human skin were grown in primary culture in a high-calcium serum-free medium that support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
2
18
2
Order By: Relevance
“…In contrast to our results, Fisher and colleagues noted no increase in either ODC mRNA or ODC enzyme activity in normal human epidermal keratinocytes, whereas both were increased in murine epidermal keratinocyte cultures [9]. Hickok and colleagues reported that PMA caused a marked decrease in ODC enzyme activity with no detectable effect on ODC mRNA levels in cultured normal and immortalized, but not tumorigenic, human keratinocytes.…”
Section: Pma and Odccontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our results, Fisher and colleagues noted no increase in either ODC mRNA or ODC enzyme activity in normal human epidermal keratinocytes, whereas both were increased in murine epidermal keratinocyte cultures [9]. Hickok and colleagues reported that PMA caused a marked decrease in ODC enzyme activity with no detectable effect on ODC mRNA levels in cultured normal and immortalized, but not tumorigenic, human keratinocytes.…”
Section: Pma and Odccontrasting
confidence: 99%
“…The observed lack of increased ODC activity in normal [3,9] or transformed human keratinocytes is consistent with the reported effect that PMA treatment has on inducing human keratinocyte differentiation [30]. PMA has been shown to induce differen-tiation in the same SV40-transformed keratinocytes studied here in parallel to an inhibition in growth [31] and in human papillomavirus (HPV) type 16 immortalized human keratinocytes [32].…”
Section: Pma and Odcsupporting
confidence: 88%
See 3 more Smart Citations